Impact of stent diameter and length on in‐stent restenosis after DES vs BMS implantation in patients needing large coronary stents—A clinical and health‐economic evaluation. Issue 1 (February 2017) - Zbinden, Rainer; von Felten, Stefanie; Wein, Bastian; Tueller, David; Kurz, David J.; Reho, Ivano; Galatius, Soren; Alber, Hannes; Conen, David; Pfisterer, Matthias; Kaiser, Christoph; Eberli, Franz R.
Summary: Aims: The British National Institute of Clinical Excellence (NICE) guidelines recommend to use drug‐eluting stents (DES) instead of bare‐metal stents (BMS) only in lesions >15 mm in length or in vessels <3 mm in diameter. We analyzed the impact of stent length and stent diameter on in‐stent restenosis (ISR) in the BASKET‐PROVE study population and evaluated the cost‐effectiveness of DES compared to BMS. Methods/Results: The BASKET‐PROVE trial compared DES vs BMS in large coronary arteries (≥3 mm). We calculated incremental cost‐effectiveness ratios (ICERs) and cost‐effectiveness acceptability curves with regard to quality‐adjusted life years (QALYs) gained and target lesion revascularizations (TLRs) avoided. A total of 2278 patients were included in the analysis. A total of 74 ISR in 63 patients were observed. In‐stent restenosis was significantly more frequent in segments treated with a BMS compared to segments treated with a DES (5.4% vs 0.76%; P <.001). The benefit of a DES compared to a BMS regarding ISR was consistent among the subgroups of stent length >15 mm and ≤15 mm, respectively. With the use of DES in short lesions, there was only a minimal gain of 0.005 in QALYs. At a threshold of 10 000 CHF per TLR avoided, DES had a high probability of being cost‐effective. Conclusion: In the BASKET‐PROVE study population, the strongest predictor of ISR is the use of a BMS, even in patients in need of stents ≥3.0 mm and ≤15 mm lesion length and DES were cost‐effective. This should prompt the NICE to reevaluate its recommendation to use DES instead of BMS only in vessels <3.0 mm and lesions >15 mm length.